Urgensi Materi Khatib Jum’at Kyai-Kyai Kampung sebagai Upaya Gerakan Deradikalisasi Agama di Kabupaten Kediri - Muslim, Ahmad Shobiri (Spiritualita, 2018)
The aims of the research is to determine the influence of khutbah jum’at material of some Islamic leaders in the several villages of Kediri-East Java in the role in minimizing the radicalism of Islam. This study includes field research based on several supporting data of observation, including; interview, participation and trining which is coverage around three mounths in the some villages on 7 districts of Kediri regency. Therefore, by analyzing the role of some Islamic leader (read; kyai) in the some Kediri villages, this research encourages that they have a so big potential in the process of giving a religious understanding to their community to minimize radicalism in Islam. This project tries to explain the role of kyai in the village is so significan in the process of de-radicalism (minimizing radicalism in Islam). The goal of this research is a finding that this potential of kyai in the some villages-Kediri should be organized and supported by several sides including; government, academic institution, and others. Hopefully, this research would like to really give a massive contribution in the process of religious radicalism in Kediri specially, and Indonesia universally.